2021
DOI: 10.4266/acc.2021.00108
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of vitamin C, thiamine, and corticosteroid therapy in adult sepsis patients: a systematic review and meta-analysis

Abstract: Background: Previous studies have suggested favorable outcomes of hydrocortisone, ascorbic acid (vitamin C), and thiamine (HAT) therapy in patients with sepsis. However, similar results have not been duplicated in sequential studies. This meta-analysis aimed to reevaluate the value of HAT treatment in patients with sepsis. Methods: Electronic databases were searched up until October 2020 for any studies that compared the effect of HAT versus non-HAT use in patients with sepsis. Results: Data from 15 studies (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Two meta-analyses regarding the effects of HAT therapy were published recently. Both Zayed et al [ 30 ] and Somagutta et al [ 31 ] concluded that HAT therapy significantly improved the SOFA score but appeared not to have significant benefits in the mortality, which was consistent with the results of this meta-analysis with a larger sample size. However, in our meta-analysis, instead of focusing on mortality, we set the change in SOFA score as the primary outcome.…”
Section: Discussionsupporting
confidence: 85%
“…Two meta-analyses regarding the effects of HAT therapy were published recently. Both Zayed et al [ 30 ] and Somagutta et al [ 31 ] concluded that HAT therapy significantly improved the SOFA score but appeared not to have significant benefits in the mortality, which was consistent with the results of this meta-analysis with a larger sample size. However, in our meta-analysis, instead of focusing on mortality, we set the change in SOFA score as the primary outcome.…”
Section: Discussionsupporting
confidence: 85%
“…Two recent meta-analyses found that both HAT therapy and the combined therapy of thiamine and Vitamin C significantly reduce the duration of vasopressor use and are associated with a reduced SOFA score on day 3. There was however insufficient data to analyse the delta SOFA scores in more detail [20,21].…”
Section: Background and Rationalementioning
confidence: 99%
“…Recent years have witnessed the expanding use of high-dose vitamin C in the management of critically ill patients with sepsis, acute respiratory distress syndrome (ARDS), cancer, and even severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia. 1 4 Vitamin C or ascorbic acid has been explored in the treatment of sepsis and septic shock because of its antioxidant properties, scavenging free radicals, and postulated bacteriostatic effect. 1 Besides, working as an enzyme cofactor for many important biological reactions, vitamin C has other proposed mechanism of actions including the prevention of mitochondrial dysfunction and septic cardiomyopathy, regulating macrophage function, and preservation of macro- or microvascular function.…”
Section: Introductionmentioning
confidence: 99%
“… 1 4 Vitamin C or ascorbic acid has been explored in the treatment of sepsis and septic shock because of its antioxidant properties, scavenging free radicals, and postulated bacteriostatic effect. 1 Besides, working as an enzyme cofactor for many important biological reactions, vitamin C has other proposed mechanism of actions including the prevention of mitochondrial dysfunction and septic cardiomyopathy, regulating macrophage function, and preservation of macro- or microvascular function. 1 , 5 Moreover, because of its potential anti-inflammatory and immune-enhancing properties, its therapeutic role has expanded well beyond the treatment of scurvy and promoted even in healthy individuals as “immune-booster”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation